Desensitizing nicotinic agents normalize tinnitus-related inhibitory dysfunction in the auditory cortex and ameliorate behavioral evidence of tinnitus - Ghimire, Madan; Cai, Rui; Ling, Lynne; Brownell, Kevin A.; Wisner, Kurt W.; Cox, Brandon C.; Hackett, Troy A.; Brozoski, Thomas J.; Caspary, Donald M. (Frontiers in Neuroscience, 2023)
Tinnitus impacts between 10-20% of the population. Individuals most troubled by their tinnitus have their attention bound to and are distracted by, their tinnitus percept. While numerous treatments to ameliorate tinnitus have been tried, no therapeutic approach has been clinically accepted. The present study used an established condition-suppression noise-exposure rat model of tinnitus to: 1) examine tinnitus-related changes in nAChR function of layer 5 pyramidal (PNs) and of vasoactive intestinal peptide (VIP) neurons in primary auditory cortex (A1); and 2) examine how the partial desensitizing nAChR agonists, sazetidine-A and varenicline, can act as potential therapeutic agents in the treatment of tinnitus. In vitro whole-cell patch-clamp studies previously revealed a significant tinnitus-related loss in nAChR-evoked excitatory postsynaptic currents from A1 layer 5 PNs. In contrast, VIP neurons from animals with behavioral evidence of tinnitus showed significantly increased nAChR-evoked excitability. Here we hypothesize that sazetidine-A and varenicline have therapeutic benefits for subjects who cannot divert their attention away from the phantom sound in their heads. We found that sazetidine-A or varenicline normalized tinnitus-related reductions in GABAergic input currents onto A1 layer 5 PNs. We then tested sazetidine-A and varenicline for the management of tinnitus using our tinnitus animal model. Subcutaneous injection of sazetidine-A or varenicline, one hour prior to tinnitus testing, significantly decreased the rat’s behavioral evidence of tinnitus in a dose-dependent manner. Collectively, these results support the need for additional clinical investigations of partial desensitizing nAChR agonists sazetidine-A and varenicline for the treatment of tinnitus.